PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DI MTS. MUHAMMADIYAH 22 PADANGSIDIMPUAN - Ramos Hidayat (Universitas Muhammadiyah Tapanuli Selatan, 2017)
In the process of learning History of Islamic Culture, there are various kinds of learning models that can be applied. Most teachers in these subjects mostly use lecture and discussion methods. However, this method is sometimes constrained by time allocation which is very difficult to create material that will be taught in accordance with the planned in karnakan material of history of Islamic culture which is solid with the number of learners which is relatively many. Discovery Learning method is widely selected Master in MTs. Muhammadiyah 22 in the process of learning. One of them on the history of Islamic culture. Hopefully with this method, it can help Teachers explain the learning materials appropriately, students can also interact with each other, ask each other in groups that have been set. Keywords: Implementation, Learning Model, Discovery Learning